Brain network and energy imbalance in Parkinson’s disease: linking ATP reduction and α-synuclein pathology - Hirohisa Watanabe; Sayuri Shima; Kazuya Kawabata; Yasuaki Mizutani; Akihiro Ueda; Akihiro Ueda; Mizuki Ito; Mizuki Ito (Frontiers in Molecular Neuroscience)
Parkinson’s disease (PD) involves the disruption of brain energy homeostasis. This encompasses broad-impact factors such as mitochondrial dysfunction, impaired glycolysis, and other metabolic disturbances, like disruptions in the pentose phosphate pathway and purine metabolism. Cortical hubs, which are highly connected regions essential for coordinating multiple brain functions, require significant energy due to their dense synaptic activity and long-range connections. Deficits in ATP production in PD can severely impair these hubs. The energy imbalance also affects subcortical regions, including the massive axonal arbors in the striatum of substantia nigra pars compacta neurons, due to their high metabolic demand. This ATP decline may result in α-synuclein accumulation, autophagy-lysosomal system impairment, neuronal network breakdown and accelerated neurodegeneration. We propose an “ATP Supply–Demand Mismatch Model” to help explain the pathogenesis of PD. This model emphasizes how ATP deficits drive pathological protein aggregation, impaired autophagy, and the degeneration of key brain networks, contributing to both motor and non-motor symptoms.